Robust synthesis of enantiopure cyclohexenyl analogues of 2/3-deoxyribose sugars as carbocyclic nucleoside precursors - Varada, Manojkumar; Kotikam, Venubabu; Kumar, Vaijayanti A. (Tetrahedron, 2011)
An expedient synthesis of 2-deoxy (10) and 3-deoxy (11) cyclohexenyl analogues of 2-deoxy and 3-deoxy-D-ribose sugar from commercially available starting materials is reported. Highly efficient enzymatic resolution of the key compound 10 is described using lipase under hydrolytic conditions. The robust methodology applied here will be useful to synthesize cyclohexenyl nucleosides, which possess potent antiviral activity and are capable of gene silencing via RNAi or antisense applications. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Carbocyclic mimics of 2-deoxy-D-ribose and 3-deoxy-D-ribose Enzymatic resolution; CeNA; DA reaction